(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The territory of Streltsovskaya Steppe was enlarged in 2004. As the result, the Natural Reserve includes lots of pasture areas and abandoned filds. Description of nine abandoned fields is given. A general features of abandoned fields distribution, together with their soil, relief, history of economic usage are elucidated.